Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan Autis Center Bengkulu - Sheyla Alviana Safitri (STIE AMKOP, 2023)
In the era of globalization, human resource issues are the focus and foundation for companies to survive. This research is an explanatory research, namely researchers who highlight the relationship between research variables and test the hypotheses that have been formulated previously. The types of data used in this study are qualitative data and quantitative data. The results of the study show that there is an effect of work motivation (X1) on employee performance (Y) Autistic Center of 0.000, thus Ho is rejected and Ha is accepted. From the significance value obtained that the X variable affects employee performance (Y). There is an effect of the work environment (X2) on employee performance (Y) Autistic Center of 0.031, thus Ho is rejected and Ha is accepted. From the significance value obtained that the variable X2 has an effect on employee performance (Y). Work motivation and work environment together influence employee performance with a Fsig value